2022
DOI: 10.1002/bse.3207
|View full text |Cite
|
Sign up to set email alerts
|

Green supply chain management in manufacturing firms: A resource‐based viewpoint

Abstract: As sustainability draws increasing attention due to the COVID-19 pandemic, interest in the green supply chain has likewise substantially increased. The present study contributes deeper insights into the logical integration of the resource-based characteristics that can facilitate the effective transition from traditional to green supply chains while also increasing the effectiveness of existing green supply chains. The proposed model, rooted in the resource-based view (RBV) theory, examines the associations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 129 publications
0
29
0
Order By: Relevance
“…From the perspective of the two theories, the study contributes by lending support for their suitability in operations and supply chain management. While RBV is already well‐grounded in the related literature (e.g., Khan et al, 2022), our study serves to broaden its application to explicate the antecedents that can positively impact business performance. To explain further, we put forth various supply chain resources categorizing them as intangible resources in RBV terminology to explain how business performance can be positively driven.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…From the perspective of the two theories, the study contributes by lending support for their suitability in operations and supply chain management. While RBV is already well‐grounded in the related literature (e.g., Khan et al, 2022), our study serves to broaden its application to explicate the antecedents that can positively impact business performance. To explain further, we put forth various supply chain resources categorizing them as intangible resources in RBV terminology to explain how business performance can be positively driven.…”
Section: Discussionmentioning
confidence: 95%
“…While RBV is already well-grounded in the related literature (e.g., Khan et al, 2022), our study serves to broaden its application to explicate the antecedents that can positively impact business performance. To…”
Section: Theoretical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Employee engagement has always been seen as a basic criterion that is positively associated with the effectiveness of a variety of corporate greening practices (Albloushi et al , 2022; ElTayeb et al , 2010; Jiang and Bansal, 2003). Employees are more willing to behave eco-actively in the workplace when organizations have an environmentally oriented management strategy and supportive policies (Khan et al , 2022; Paillé et al , 2014). This therefore suggested that OCB toward the environment might also be important.…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%
“…on the ecosystem and guarantee the wellbeing of their personnel (Sharma, Jabbour, & de Sousa Jabbour, 2020) However, in today's context, firms must not only comply with environmental and social regulations but also are called to refine the manufacturing process, reduce waste, and procure continuous improvement (Khan et al, 2022), while addressing numerous internal and external risks that ultimately prompt production shutdowns, capricious markets, and performance decline (Chan et al, 2017). On the other hand, following the COVID-19 pandemic, digital transformation (DT) is hastening in every industry as a novel way to face operational challenges and overcome the manufacturing and supply chains' (SCs) weaknesses that have been aggravated in this particular context.…”
mentioning
confidence: 99%